2016
DOI: 10.1080/13562517.2015.1115970
|View full text |Cite
|
Sign up to set email alerts
|

Exploring teachers’ inquiry-based attitude

Abstract: Exploring Teachers' Inquiry-Based AttitudeHaving a well-founded insight into the characteristics of teachers Inquiry-Based Attitude (IA) supports operationalizing IA as a learning goal in Teacher Education. The aim of this study is to refine the notion of IA from an ill-defined global concept into something with reliable and valid characteristics. To do so, data was gathered on three different occasions amongst three different cohorts of teachers who participated in a master's programme at a Dutch university f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 38 publications
1
16
0
3
Order By: Relevance
“…According to this model, teacher professional growth occurs when change in one domain leads to change in another through the processes of enactment or reflection. The importance of critical reflection for deep professional learning has also been emphasised elsewhere in the literature (Avalos, 2011;Meijer, Geijsel, Kuijpers, Boei, & Vrieling, 2016;Mezirow & Taylor, 2009). Further, it has been found that in order for deep learning to occur, the following are necessary: experiencing situations in an unbiased manner; observing and reflecting from multiple perspectives; and constructing and using theories or concepts for problem solving or decision making (Meijer et al, 2016).…”
Section: Theoretical Background Teacher Learning and Professional Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…According to this model, teacher professional growth occurs when change in one domain leads to change in another through the processes of enactment or reflection. The importance of critical reflection for deep professional learning has also been emphasised elsewhere in the literature (Avalos, 2011;Meijer, Geijsel, Kuijpers, Boei, & Vrieling, 2016;Mezirow & Taylor, 2009). Further, it has been found that in order for deep learning to occur, the following are necessary: experiencing situations in an unbiased manner; observing and reflecting from multiple perspectives; and constructing and using theories or concepts for problem solving or decision making (Meijer et al, 2016).…”
Section: Theoretical Background Teacher Learning and Professional Growthmentioning
confidence: 99%
“…Their enactment of new knowledge, attitudes, or beliefs then leads to changes in practice. However, it also suggests that some of the components necessary for deep learning as described by Meijer et al (2016) are missing (e.g., critical reflection, using theories to solve problems). Indeed, research suggests that experience alone is not enough to ensure teacher growth or effective changes to teachers' pedagogies.…”
Section: Theoretical Background Teacher Learning and Professional Growthmentioning
confidence: 99%
“…IA-External relates to active knowledge-sourcing behaviour focused on professional development in response to specific questions and/or problems (Meijer et al, 2016). This means that a person actively seeks new relevant knowledge sources in response to specific questions.…”
Section: Stimulating An Inquiry-based Attitudementioning
confidence: 99%
“…IA-Internal concerns the ability of teachers to gain 'new modes of understanding' about themselves, about knowledge and about the context, with the purpose to work on/refresh their professional behaviour (Meijer, Geijsel, Kuijpers, Boei, & Vrieling, 2016). …”
Section: Stimulating An Inquiry-based Attitudementioning
confidence: 99%
“…The first process involves learners' judgements and evaluations of their performance of the task. For higher education students this ability to reflect effectively is considered an important twenty-first century skill (Power 2016) because it enables students to acquire new professional modes of understanding and behavior (Meijer et al 2016). TCs can learn to make judgments about the way their work relates to the criteria.…”
Section: Coaching/judgingmentioning
confidence: 99%